Dual Effects of Nanostructuring and Oxygen Vacancy on Photoelectrochemical Water Oxidation Activity of Superstructured and Defective Hematite Nanorods. Issue 14 (27th February 2018) - Wang, Lei; Marcus, Kyle; Huang, Xiaojuan; Shen, Zhiqiang; Yang, Yang; Bi, Yingpu
Abstract: An Ar atmospheric treatment is rationally used to etch and activate hematite nanoflakes (NFs) as photoanodes toward enhanced photoelectrochemical water oxidation. The formation of a highly ordered hematite nanorods (NRs) array containing a high density of oxygen vacancy is successfully prepared through in situ reduction of NFs in Ar atmosphere. Furthermore, a hematite (104) plane and an iron suboxide layer at the absorber/back‐contact interface are formed. The material defects produced by a thermal oxidation method can be critical for the morphology transformation from 2D NFs to 1D NRs. The resulting hematite NR photoanodes show high efficiency toward solar water splitting with improved light harvesting capabilities, leading to an enhanced photoresponse due to the artificially formed oxygen vacancies. Abstract : A high degree of ordering in hematite nanorods with significant photoelectrochemical activity . An Ar atmosphere treatment is used to etch and activate "defect" hematite nanoflakes into 1D nanorods. The resulting hematite nanorods serve as a photoanode for highly efficient solar water splitting with an excellent photoresponse due to a higher light harvesting range and incorporation of oxygen vacancies.